Augmented Culture - Daniel Dendra (Oz, 2011)
At anOther Architect (aA), we exploit a chameleon-like strategy, in which discourse with the client and the specifics of site and culture influence design decisions. Bringing this architectural method to each project, we offer each client a fresh look at normative situations in everyday life.